Polish ethics and medicine in XXI century (opportunities and threats) - Sytnik-Czetwertyński, Janusz; Skowron, Adam; Pinkas, Jarosław; Ostrowski, Janusz (Wiedza Medyczna, 2022)
Despite medical breakthroughs, mankind is still unable to effectively counter health challenges. The COVID-19 pandemic is a case in point. It has failed to predict its effects and the extent to which it is spreading, even though statistical studies hade indicated that it may be coming. The purpose of this article is to identify medical and ethical issues arising from the difference between the current state of medical knowledge and the associated challenges.